The Power of Law To Buy Land A Knock-Off Who Is Not Recognized For Sale Bought It By A Vendor’s Heir - Tutiek Retnowati; Widyawati Boediningsih (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
This study aims to findout and analyzed the form of proof of Proof in the deed Onderhands has the same power as an authentic deed if the content of the deed is not denied by the parties or in the other words acknowledge and do not deny the truth of what is written and the signatures of the parties in the agreement. The research method in this study uses normative research methods and uses a statute approach and conceptual approach. The result of this research is that in accordance with article 1857 BW, The power of proof of a deed underhand can be equated with an authenthic deed. A Buying and Selling agreement using a deed onderhands is valid if examined in article 1320 BW because it has fulfilled the elements in the legal requirements of the agreement. Second, Efforts to resolve disputes that can be carried out by the buyers is by filling a lawsuit for default at the distirct court, because the absolute requirement for making a Buying and Selling deed (AJB) by PPAT must be attended by the parties concerned. The panel of judges can issue a decision by giving permission to the buyer to register Petok D through a Buying and Selling in order to be able to take care of the transfer of name without the participation of the heirs in order to register a certificate of Land rights at the office of the national defense Agency.